The Subtitling Strategies in God’s Not Dead 2 Movie - Arni Simatupang; Elisabeth Sagala; Surya Tampubolon; Nenni Triana Sinaga; Harpen Silitonga (Institute of Computer Science (IOCS), 2022)
This study focused on the analysis of source language into target language in subtitling strategies in the film God's Not Dead 2. This study aims to find subtitle strategies for each translation of the dialogue text in the film God's Not Dead. This research also focuses on applying Gottlieb's theory which consist of ten strategies, they are: paraphrase, imitation, condensation, transcription, transfer, dislocation, decimation,expansion, deletion, resignation. After done that, the method that used to analyzed the data is using descriptive qualitative method. The researcher found which strategy dominated the translation of God's Not Dead 2 movie. The findings showed that there were seven strategies out of ten applied by translator in translating subtitle from source language into target language, they were:paraphrase strategy for 118 frequency (30%), transfer strategy for 80 frequency (20%), imitation strategy for 77 frequency (19.5%), condensation strategy for 40 frequency (10.1), expansion strategy for 6 frequency (1.5%), decimation strategy for 4 frequency (1%), and the last is deletion strategy for 2 frequency (0.5%). The researchers also find out 3 strategies unused in this subtitling strategies of God's Not Dead 2 movie, they are transcription strategy, dislocation strategy, and the last is resign strategy. The researchers concluded that paraphrase strategy was the most dominant uses with the highest frequency uses in God's Not Dead 2 movie and following with the second highest subtitling strategy was frequently used by the translator is transfer strategy.